Returns to education and wage differentials in Malaysia - Mohd Arshad, Mohd Nahar; Mat Ghani, Gairuzazmi (Tennessee State University, 2015)
The main objective of this study is to estimate the effects of education on earnings of Malaysians. To achieve the objective, a Mincerian earning function has been estimated using Malaysia’s Household Income Survey 2009. Apart from considering levels of qualification, factors such as age, marital status, ethnicity, occupational types and geographical locations have been considered in the estimations. The results show that the rates of return in Malaysia are high and positive, especially at the upper secondary and university education levels. Male workers, on average, received 40.3% higher than their female counterparts, holding other factors constant. There is also significant evidence of wage differential attributable to regional/urban-rural locations in Malaysia. By occupational activities, our estimates suggest that employers received the highest income, followed by those in public service, private sector, and then self-employed workers. Wage differential in Malaysia is also explained by ethnicity.